High strength and heat stable nickel-based alloy

A nickel-based alloy with tailored compositions addresses the challenges of high-temperature strength and corrosion resistance in A-USC boiler environments, demonstrating improved mechanical properties and cost-effectiveness by leveraging gamma prime and TCP phases, and controlled microstructural refinement.

CN116981788BActive Publication Date: 2025-03-18HUNTINGTON ALLOYS CORP (US)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280021283.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-13
Filing Date
2022-01-13
Publication Date
2025-03-18
Estimated Expiration
2042-01-13

AI Technical Summary

Technical Problem

Existing high-temperature alloys for advanced ultra-supercritical (A-USC) boilers face challenges in balancing room temperature ductility and high-temperature strength, as well as corrosion resistance, particularly in environments where traditional nickel-chromium and nickel-cobalt alloys fall short.

Method used

A nickel-based alloy composition is developed, including specific ranges of aluminum, cobalt, chromium, iron, molybdenum, niobium, tungsten, and carbon, which provides enhanced high-temperature strength, ductility, and corrosion resistance through a combination of gamma prime (γ') and topological close-packed (TCP) phase stabilization, along with controlled carbon and minor element additions for microstructural refinement.

Benefits of technology

The alloy exhibits improved high-temperature strength, ductility, and resistance to corrosion, with specific examples showing enhanced stress rupture life, elongation, and impact energy at 700°C, while maintaining competitive cost and processing characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116981788B_ABST
    Figure CN116981788B_ABST
Patent Text Reader

Abstract

The present application relates to an alloy comprising, by weight percentage, about 1.3% to about 1.8% aluminum, about 1.5% to about 4.0% cobalt, about 18.0% to about 22.0% chromium, about 4.0% to about 10.0% iron, about 1.0% to about 3.0% molybdenum, about 1.0% to about 2.5% niobium, about 1.3% to about 1.8% titanium, about 0.8% to about 1.2% tungsten, about 0.01% to about 0.08% carbon, and the balance nickel and incidental impurities. The alloy has a stress rupture life of at least 300 hours at a temperature of 700°C and a pressure of 393.7 MPa (57.1 ksi), and the alloy has a room temperature elongation of at least 15% after aging at 700°C for 1000 hours.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of U.S. Patent Application No. 63 / 136,668, filed on January 13, 2021. The disclosure of the above application is incorporated herein by reference. Technical Field

[0003] The present invention relates to nickel-based alloys and, more particularly, to high strength, thermally stable nickel-based alloys for use at elevated temperatures. Background Art

[0004] The statements in this section merely provide background information related to the present application and may not constitute prior art.

[0005] Alloys used in harsh environments such as advanced ultra-supercritical (A-USC) boilers require a combination of ductility at room temperature for workability, and strength and oxidation resistance at temperatures approaching 815°C (1500°F) when in service. Therefore, conventional alloys use a combination of nickel and chromium to improve high temperature oxidation resistance, a combination of titanium, aluminum, and niobium to improve high temperature strength through precipitation hardening, and a combination of nickel and cobalt to improve ductility at room temperature and after the alloy has been in service at elevated temperatures to fabricate and repair the alloy.

[0006] The present application addresses the problem of strength and ductility required for alloys used in A-USC boilers, as well as other problems associated with nickel-based precipitation-hardenable alloys used in high temperature corrosive environments. Summary of the invention

[0007] This section provides a general summary of the application and is not intended to be a comprehensive disclosure of its full scope or all of its features.

[0008] In an embodiment of the present application, the alloy comprises a composition, which composition, by weight percentage (unless otherwise specified, weight percentage is used throughout), includes: about 1.3% to about 1.8% aluminum, about 1.5% to about 4.0% cobalt, about 18.0% to about 22.0% chromium, about 4.0% to about 10.0% iron, about 1.0% to about 3.0% molybdenum, about 1.0% to about 2.5% niobium, about 1.3% to about 1.8% titanium, about 0.8% to about 1.2% tungsten, about 0.01% to about 0.08% carbon, and the balance nickel and incidental impurities. In some embodiments, the alloy has a stress rupture life of at least 300 hours at a temperature of 700°C and a pressure of 393.7 MPa (57.1 ksi), and a room temperature elongation of at least 15% after 1000 hours at a temperature of 700°C.

[0009] In some embodiments, the alloy contains cobalt in an amount of about 2.0% to about 3.0%. In at least one embodiment, the alloy contains molybdenum in an amount of about 1.0% to about 2.75%. In some embodiments, the alloy contains niobium in an amount of about 1.0% to about 1.75%.

[0010] In at least one embodiment, the alloy contains cobalt at a content of about 2.0% to about 3.0%, and molybdenum at a content of about 1.0% to about 2.75%. In some embodiments, the alloy contains cobalt at a content of about 2.0% to about 3.0%, and niobium at a content of about 1.0% to about 1.75%.

[0011] In at least one embodiment, the alloy includes molybdenum in an amount of about 1.0% to about 2.75% and niobium in an amount of about 1.0% to about 1.75%.

[0012] In some embodiments, the alloy includes cobalt in an amount of about 2.0% to about 3.0%, molybdenum in an amount of about 1.0% to about 2.75%, and niobium in an amount of about 1.0% to about 1.75%.

[0013] In at least one embodiment, the alloy has a stress rupture life of at least 500 hours at a temperature of 700° C. and a pressure of 393.7 MPa (57.1 ksi).

[0014] In some embodiments, the alloy has a room temperature elongation of at least 20% after aging at 700°C for 1000 hours. In at least one embodiment, the alloy has a room temperature elongation of at least 22% after aging at 700°C for 1000 hours.

[0015] In at least one embodiment, the alloy has a room temperature elongation of at least 15% after aging at 700°C for 5000 hours. In some embodiments, the alloy has a room temperature elongation of at least 20% after aging at 700°C for 5000 hours.

[0016] In some embodiments, the alloy has a room temperature impact energy of at least 12 ft-lb after aging at 700°C for 1000 hours. In at least one embodiment, the alloy has a room temperature impact energy of at least 15 ft-lb after aging at 700°C for 1000 hours. In some embodiments, the alloy has a room temperature impact energy of at least 20 ft-lb after aging at 700°C for 1000 hours.

[0017] In at least one embodiment, the alloy has a room temperature impact energy of at least 10 ft-lb after aging at 700°C for 5000 hours. In some embodiments, the alloy has a room temperature impact energy of at least 12 ft-lb after aging at 700°C for 5000 hours. In at least one embodiment, the alloy has a room temperature impact energy of at least 15 ft-lb after aging at 700°C for 5000 hours.

[0018] In some embodiments, the room temperature (RT) ultimate tensile strength of the alloy is between about 160 ksi (1104 MPa) and about 175 ksi (1207 MPa), the room temperature (RT) 0.2% yield strength of the alloy is between about 95 ksi (655 MPa) and 115 ksi (793 MPa); and the room temperature elongation of the alloy is between about 30% and about 45% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling. In at least one embodiment, the room temperature ultimate tensile strength is between about 160 ksi (1104 MPa) and about 170 ksi (1172 MPa), the room temperature 0.2% yield strength is between about 95 ksi (655 MPa) and 110 ksi (758 MPa); and the room temperature elongation of the alloy is between about 35% and about 45% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling.

[0019] In some embodiments, the room temperature ultimate tensile strength is between about 175 ksi (1207 MPa) and about 195 ksi (1344 MPa), the room temperature 0.2% yield strength is between about 105 ksi (724 MPa) and 125 ksi (861 MPa); and the room temperature elongation is between about 15% and about 30% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling and aging at 700°C (1292°F) for 1000 hours and air cooling. In at least one embodiment, the room temperature ultimate tensile strength is between about 175 ksi (1207 MPa) and about 185 ksi (1275 MPa), the room temperature 0.2% yield strength is between about 105 ksi (724 MPa) and 120 ksi (827 MPa); and the room temperature elongation of the alloy is between about 22% and about 30% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling, and aging at 700°C (1292°F) for 1000 hours and air cooling.

[0020] In some embodiments, the room temperature ultimate tensile strength is between about 170 ksi (1172 MPa) and about 200 ksi (1379 MPa), the room temperature 0.2% yield strength is between about 100 ksi (689 MPa) and about 120 ksi (827 MPa); and the room temperature elongation of the alloy is between about 16% and about 30% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling and aging at 700°C (1292°F) for 5000 hours and air cooling. In at least one embodiment, the room temperature ultimate tensile strength is between about 175 ksi (1207 MPa) and about 190 ksi (1310 MPa), the room temperature 0.2% yield strength is between about 105 ksi (724 MPa) and 115 ksi (793 MPa); and the room temperature elongation of the alloy is between about 20% and about 30% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling, and aging at 700°C (1292°F) for 5000 hours and air cooling.

[0021] In some embodiments, the alloy has an ultimate tensile strength at 700°C between about 130 ksi (896 MPa) and about 155 ksi (1069 MPa), a 0.2% yield strength at 700°C between about 90 ksi (620 MPa) and about 105 ksi (724 MPa); and an elongation at 700°C between about 9% and about 25% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling. In at least one embodiment, the alloy has an ultimate tensile strength at 700°C between about 125 ksi (861 MPa) and about 140 ksi (965 MPa), a 0.2% yield strength at 700°C between about 90 ksi (620 MPa) and about 100 ksi (689 MPa); and an elongation at 700°C between about 14% and about 20% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling.

[0022] In some embodiments, the alloy has an ultimate tensile strength at 700°C between about 135 ksi (931 MPa) and about 155 ksi (1069 MPa), a 0.2% yield strength at 700°C between about 95 ksi (655 MPa) and about 110 ksi (758 MPa), and an elongation at 700°C between about 12% and about 30% after annealing the alloy at 788°C (1450°F) for 4 hours followed by air cooling and aging at 700°C (1292°F) for 1000 hours followed by air cooling. In at least one embodiment, the alloy has an ultimate tensile strength at 700°C between about 135 ksi (931 MPa) and about 150 ksi (1034 MPa), a 0.2% yield strength at 700°C between about 95 ksi (655 MPa) and about 105 ksi (724 MPa); and an elongation at 700°C between about 15% and about 30% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling, and aging at 700°C (1292°F) for 1000 hours and air cooling.

[0023] In some embodiments, the alloy has an ultimate tensile strength at 700°C between about 130 ksi (896 MPa) and about 150 ksi (1034 MPa), a 0.2% yield strength at 700°C between about 90 ksi (620 MPa) and about 110 ksi (758 MPa); and an elongation at 700°C between about 15% and about 28% after annealing the alloy at 788°C (1450°F) for 4 hours followed by air cooling and aging at 700°C (1292°F) for 5000 hours followed by air cooling. In at least one embodiment, the alloy has an ultimate tensile strength at 700°C between about 130 ksi (896 MPa) and about 145 ksi (1000 MPa), a 0.2% yield strength at 700°C between about 90 ksi (620 MPa) and about 102 ksi (703 MPa); and an elongation at 700°C between about 15% and about 25% after annealing the alloy at 788°C (1450°F) for 4 hours and air cooling, and aging at 700°C (1292°F) for 5000 hours and air cooling.

[0024] In some embodiments, the alloy includes a composition comprising, by weight percentage: about 0.02% to about 0.3% manganese; about 0.05% to about 0.3% silicon; about 0.005% to about 0.2% vanadium; about 0.005% to about 0.2% zirconium; about 0.001% to about 0.025% boron; and about 0.001% to about 0.02% nitrogen.

[0025] In another embodiment of the present application, the alloy includes a composition, which consists essentially of, by weight percentage, about 1.3% to about 1.8% aluminum, about 0.001% to about 0.025% boron, about 0.01% to about 0.08% carbon, about 2.0% to about 3.0% cobalt, about 18.0% to about 22.0% chromium, about 4.0% to about 10.0% iron, about 0.02% to about 0.3% manganese, about 1.0% to about 3.0% molybdenum, about 1.0% to about 2.5% niobium, about 0.001% to about 0.02% nitrogen, about 0.05% to about 0.3% silicon, about 1.3% to about 1.8% titanium, about 0.8% to about 1.2% tungsten, about 0.005% to about 0.2% vanadium, about 0.005% to about 0.2% zirconium, and the balance nickel and incidental impurities. In some embodiments, the alloy has a stress rupture life of at least 300 hours at 700°C and 393.7 MPa (57.1 ksi) and a room temperature elongation of at least 15% after aging at 700°C for 1000 hours.

[0026] Further areas of applicability will become apparent from the description provided in this specification.It should be understood that these descriptions and specific examples are for illustrative purposes only and are not intended to limit the scope of this application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to better understand the present application, various forms of the present application will now be described by way of example with reference to the accompanying drawings, in which:

[0028] Figure 1 Shown is a SEM micrograph depicting the microstructure of a high strength, thermally stable nickel-based alloy according to the teachings of the present application.

[0029] Figure 2 Shown at higher magnification Figure 1 A portion of a micrograph in FIG, with multiple locations identified by energy dispersive spectroscopy (EDS) analysis.

[0030] Figure 3 Shows Figure 1 and Figure 2 EDS analysis results of a part of the microstructure.

[0031] The drawings described herein are for illustration purposes only and are not intended to limit the scope of the present application in any way. DETAILED DESCRIPTION

[0032] The following description is merely exemplary in nature and is not intended to limit the present application, application or use. It should be understood that throughout the drawings, corresponding reference numerals indicate similar or corresponding parts and features. It should be understood that, unless otherwise indicated, the composition values ​​in the present application are expressed in weight percentage (hereinafter referred to as "wt.%" or simply "%").

[0033] Table 1 shows the compositions of eighteen (18) experimental heats (Heats 1-18) and one heat (Heat 19) of a commercial alloy. Brand Nichrome, more specifically, used for Brand (hereinafter referred to as "Alloy 740H"). Table 2 shows another three experimental heats (Heats 20-22).

[0034] The experimental alloy includes a series of carbon (C), iron (Fe), silicon (Si), nickel (Ni), chromium (Cr), aluminum (Al), titanium (Ti), cobalt (Co), molybdenum (Mo), niobium (Nb), and tungsten (W). In addition, small amounts (i.e., less than about 0.10% by weight) of manganese (Mn), sulfur (S), copper (Cu), tantalum (Ta), phosphorus (P), boron (B), vanadium (V)), and zirconium (Zr) are included as impurities, trace elements, deoxidizing elements, and / or grain boundary strengthening additives, which will be discussed in more detail below. In addition, calcium (Ca), magnesium (Mg), and rare earth metals (e.g., cesium, lanthanum, yttrium, etc.) may be present as trace elements with desulfurization and deoxidation properties.

[0035]

[0036] Table 1

[0037]

[0038] Table 2

[0039] Carbon (C) is added to control grain growth during processing and to increase creep strength. Excessive grain boundary carbides can impair the ductility of the alloy in the present application. In addition, the primary MC-type carbides formed with niobium and titanium can form a large number of fine veins and also affect the amount of γ′ strengthening phase that can be formed. Therefore, the amount of C is between about 0.005% and about 0.1%. In some embodiments, the amount of C in the alloy is between about 0.0075% and about 0.075%, for example, between about 0.01% and about 0.075%. In at least one embodiment, the amount of C in the alloy is between about 0.01% and about 0.05%.

[0040] Manganese (Mn) is added as a deoxidizer. However, excessive Mn will impair the thermal stability and ductility of the alloy in the present application. Therefore, the amount of Mn is between about 0.05% and about 0.3%. In some embodiments, the amount of Mn in the alloy is between about 0.075% and about 0.25%, for example, between about 0.075% and about 0.2%. In at least one embodiment, the amount of Mn in the alloy is between about 0.09% and about 0.15%.

[0041] Iron (Fe) is added to reduce the production cost of the alloy. However, excessive Fe additions will impair the thermal stability and ductility of the alloy in the present application. Therefore, the amount of Fe is between about 3.0% and about 15.0%. In some embodiments, the amount of Fe in the alloy is between about 4.0% and about 12.5%, for example, between about 4.0% and about 10.0%. In at least one embodiment, the amount of Fe in the alloy is between about 4.0% and about 9.0%, for example, between about 5.0% and about 10.0%.

[0042] Similar to Mn, silicon (Si) is added as a deoxidizer. However, excessive Si can impair the weldability, thermal stability and ductility of the alloy in the present application. Therefore, the amount of Si is between about 0.05% and about 0.3%. In some embodiments, the amount of Si in the alloy is between about 0.075% and about 0.25%, for example, between about 0.1% and about 0.2%. In at least one embodiment, the amount of Si in the alloy is between about 0.11% and about 0.18%.

[0043] Nickel (Ni) improves metallurgical stability, high temperature corrosion resistance and weldability. In addition, nickel is used to form a γ' strengthening phase.

[0044] Chromium (Cr) is added to enhance high temperature corrosion resistance. However, excessive Cr additions can impair high temperature strength and promote the formation of harmful σ phases in the alloys of the present application. Therefore, the amount of Cr is between about 17.0% and about 23.0%. In some embodiments, the amount of Cr in the alloy is between about 18.0% and about 22.0%, such as between about 19.0% and about 21.0%.

[0045] Aluminum (Al) is added to form γ' phase Ni3Al. However, excessive Al additions will impair the hot formability of the alloy in the present application. Therefore, the amount of Al is between about 1.0% and about 2.5%. In some embodiments, the amount of Al in the alloy is between about 1.1% and about 2.0%, such as between about 1.3% and about 1.9%. In at least one embodiment, the amount of Al in the alloy is between about 1.2% and about 1.8%, such as between about 1.3% and about 1.9%.

[0046] Titanium (Ti) is also added to form the γ' phase and can replace Al. However, excessive Ti additions can impair the hot formability of the alloy in the present application. Therefore, the amount of Ti is between about 1.0% and about 2.5%. In some embodiments, the amount of Ti in the alloy is between about 1.1% and about 2.0%, such as between about 1.3% and about 1.9%. In at least one embodiment, the amount of Ti in the alloy is between about 1.2% and about 1.8%, such as between about 1.3% and about 1.9%.

[0047] Cobalt (Co) enhances high temperature strength and is associated with improved fracture ductility. However, excessive Co additions increase the cost of the alloy of the present application. Therefore, the amount of Co is between about 1.0% and about 3.0%. In some embodiments, the amount of Co in the alloy is between about 1.5% and about 3.0%, for example, between about 1.6% and about 3.0%. In at least one embodiment, the amount of Co in the alloy is between about 1.7% and about 3.0%, for example, between about 1.8% and about 3.0%.

[0048] Molybdenum (Mo) provides a solid solution strengthening effect, thereby improving high temperature fracture strength. However, excessive Mo additives can lead to the formation of a topological close packing (TCP) phase, which can impair the ductility of the alloy in the present application after long-term exposure to high temperatures. Therefore, the amount of Mo is between about 0.8% and about 3.5%. In some embodiments, the amount of Mo in the alloy is between about 1.0% and about 3.0%, for example, between about 1.0% and about 2.9%. In at least one embodiment, the amount of Mo in the alloy is about 1.0% to about 2.8%, for example, about 1.0% to about 2.7%.

[0049] Niobium (Nb) is added for solid solution strengthening and can replace Al in the γ′ phase. However, excessive Nb additions will impair the hot formability, ductility and impact strength of the alloy in the present application after long-term exposure to high temperatures. Therefore, the amount of Nb is between about 1.0% and about 3.0%. In some variations, the amount of Nb in the alloy is between about 1.0% and about 2.8%, for example, between about 1.0% and about 2.7%. In at least one embodiment, the amount of Nb in the alloy is between about 1.0% and about 2.6%, preferably between about 1.2% and about 2.7%. It should be understood that in some embodiments of the present application, tantalum (Ta) replaces part or all of Nb. For example, in at least one embodiment, Nb is less than 1.0% and Ta is added to 1.0%.

[0050] Boron (B) and zirconium (Zr) additives provide grain boundary strengthening and improve high temperature ductility. However, excessive B and / or Zr additives can damage the hot formability and weldability of the alloy in the present application. Therefore, the amount of B is about 0.001% to about 0.025%. In some embodiments, the amount of B in the alloy is between about 0.002% to about 0.02%, for example, between about 0.003% to about 0.015%. In at least one embodiment, the amount of B is between about 0.003% and about 0.01%. In addition, the amount of Zr is between about 0.001% to about 0.05%. In some embodiments, the amount of Zr in the alloy is between about 0.005% to about 0.04%, for example, between about 0.0075% and about 0.03%. In at least one embodiment, the amount of Zr is between about 0.01% to about 0.02%.

[0051] Similar to Mo, tungsten (W) provides a solid solution strengthening effect, thereby enhancing high temperature fracture strength. However, excessive W additives can lead to the formation of TCP (topological close packing) phases, which can damage the alloy in the present application after long-term exposure to high temperatures. Therefore, the amount of W is between about 0.75% and about 2.0%. In some embodiments, the amount of W in the alloy is between about 0.8% and about 1.5%, for example, between about 0.9% and about 1.3%. In at least one embodiment, the amount of W in the alloy is between about 0.9% and about 1.2%, for example, between about 0.8% and about 1.2%.

[0052] It should also be understood that the element range discussed herein includes all increments between the minimum alloying element composition value and the maximum alloying element composition value. That is, the scope of the minimum alloying element composition value can be from a minimum value to a maximum value. Similarly, the scope of the maximum alloying element composition value can be from the maximum value shown to the minimum value discussed. For example, the minimum Ti content can be any value between 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 and these increments, and the maximum Ti content can be any value between 2.5, 2.4, 2.3, 2.2, 2.1, 2.0, 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, 1.2, 1.1, 1.0 and these increments.

[0053] Still referring to Tables 1 and 2, Heats 2, 5, 6, 7, 10, 12, and 20-22 are examples of compositions according to the teachings of the present application. In particular, Heats 2, 5, 6, 7, 10, 12, and 20-22 have chemical compositions within the teachings of the present application. In addition, Heats 2, 5, 6, 7, 10, 12, and 20-22 have at least one desired property in terms of cost, mechanical strength, ductility, thermal stability, and / or high temperature corrosion.

[0054] In some embodiments of the present application, alloys according to the teachings of the present application have a combination of desirable properties with respect to cost, mechanical strength, ductility, and / or high temperature corrosion, as discussed in more detail below.

[0055] The experimental alloys were melted in a vacuum induction melting (VIM) furnace and cast into 4 inch (10.2 cm) diameter molds to form 50 pound (22.7 kg) ingots. The ingots were heated at 2200°F (1204°C) for 16 hours, then the temperature was reduced to 2100°F (1149°C) for initial hot rolling, and reheated at 2075°F (1135°C) for additional hot rolling until 0.5 inch (1.27 cm) thick hot rolled plates were produced. The 0.5 inch (1.27 cm) thick hot rolled plates were "solution annealed" at 2000°F (1093°C) for 1 hour and water quenched, then "aged" at 1450°F (788°C) for 4 hours and air cooled. The grain size of all experimental heats examined in this "solution annealed + aged" condition was ASTM #2-4.

[0056] The commercial alloy heat (i.e., Heat 19) was initially hot rolled at 2100°F (1149°C) from 1.5 inch (3.8 cm) commercial plate and reheated at 2075°F (1135°C) during processing of the material into 0.5 inch (1.27 cm) thick hot rolled plate. The 0.5 inch (1.27 cm) thick hot rolled plate of Heat 19 was solution annealed at 2025°F (1107°C) for 1 hour, then water quenched and aged at 1472°F (800°C) for 4 hours and air cooled. The grain size of all commercial alloy heat samples examined in this solution annealed + aged condition also reached ASTM #2-4.

[0057] In addition to the samples of the heats shown in Tables 1 and 2 that were provided (and tested) under the above-mentioned solution annealed + aged conditions, some of the solution annealed + aged samples were aged for an additional 1000 hours at 700°C (1292°F) ("700°C / 1000h / AC") and then air cooled, or aged for an additional 5000 hours at 700°C (1292°F) ("700°C / 5000h / AC") and then air cooled. Therefore, the samples were tested under the conditions of solution annealing + aging, solution annealing + aging + 700°C / 1000h / AC (also referred to herein as “700°C / 1000h / AC condition” or “700°C / 1000h / AC sample”), and solution annealing + aging + 700°C / 5000h / AC (also referred to herein as “700°C / 5000h / AC condition” or “700°C / 5000h / AC sample”).

[0058] Tables 3 and 4 show room temperature (RT) tensile data for samples tested in the solution annealed + aged condition.

[0059] Heat UTS, KSI UTS,MPa YS, KSI YS, MPa Elong. ROA Alloy 1 164.7 1135.6 103.3 712.3 37.6 41.9 Alloy 2 162.8 1122.5 103.4 712.9 40 41.6 Alloy 3 165.1 1138.4 104.3 719.1 38.1 41.8 Alloy 4 166.9 1150.8 106.9 737.1 38.6 43.6 Alloy 5 160.8 1108.7 98.7 680.5 40.9 42.6 Alloy 6 163.1 1124.6 101.4 699.2 39.3 42.1 Alloy 7 169.3 1167.3 102.7 708.1 35 37 Alloy 7 167.8 1157.0 99.8 688.1 36 41 Alloy 8 165.4 1140.4 103.8 715.7 36.8 41.8 Alloy 9 171.8 1184.6 110.3 760.5 31 28 Alloy 10 171.4 1181.8 109.4 754.3 35 38 Alloy 11 171.9 1185.3 107 737.8 33 41 Alloy 12 170.1 1172.8 107.8 743.3 35 39 Alloy 13 172.6 1190.1 106.1 731.6 34 40 Alloy 14 169.7 1170.1 104.2 718.5 34 40 Alloy 15 164.3 1132.8 95.1 655.7 40 46 Alloy 15 166.2 1145.9 97.5 672.3 39 42 Alloy 16 166.4 1147.3 98.2 677.1 37 43 Alloy 17 176.6 1217.7 109.3 753.6 33 39 Alloy 18 172.2 1187.3 105.5 727.4 27 29 Alloy 18 174 1199.7 105.2 725.4 35 37 Alloy 19 167.5 1154.9 103.6 714.3 37 45

[0060] Table 3

[0061] Heat UTS, ksi UTS, MPa YS, KSI YS, MPa Elong. ROA Heat 22 171.8 1184.6 109.5 755.0 33.9 41.7 Heat 22 170.9 1178.4 109.7 756.4 34 40.7 Heat 21 167.8 1157 102.3 705.4 34.8 40.7 Heat 21 167.5 1154.7 103.5 713.6 38.4 45.3 Heat 20 164.2 1132.2 102.1 703.8 38.4 44 Heat 20 165.6 1142.1 103.2 711.5 38.4 45.3

[0062] Table 4

[0063] As shown in Tables 3 and 4, the heats having compositions within the teachings of the present application (i.e., Heats 2, 5, 6, 7, 10, 12, and 20-21) had a minimum room temperature (RT) ultimate tensile strength (UTS) of 1108.7 MPa (160.8 ksi), a minimum room temperature (RT) 0.2% yield strength (YS) of 680.5 MPa (98.7 ksi), a minimum room temperature (RT) elongation of 35%, and a minimum room temperature (RT) reduction in area (ROA) of 37%. That is, in some embodiments, the minimum room temperature (RT) ultimate tensile strength (UTS) of the alloy having a composition within the teachings of the present application in the solution annealing + aging condition is 1108.7 MPa (160.8 ksi), the minimum room temperature (RT) yield strength (YS) is 680.5 MPa (98.7 ksi), the minimum room temperature (RT) elongation is 35%, and the minimum room temperature (RT) area reduction percentage (ROA) is 37%. In comparison, the room temperature (RT) elongation of Heat 9 in the solution annealing + aging condition is 31%, and the room temperature (RT) area reduction percentage (ROA) is 28%; the room temperature (RT) elongation of Heat 11 in the solution annealing + aging condition is 33%; the room temperature (RT) elongation of Heat 13 in the solution annealing + aging condition is 34%; and the room temperature (RT) elongation of Heat 17 in the solution annealing + aging condition is 33%.

[0064] In addition, the room temperature (RT) ultimate tensile strength (UTS) of commercial alloy heat 19 is 1154.9 MPa (167.5 ksi), the room temperature (RT) 0.2% yield strength (YS) is 714.3 MPa (103.6 ksi), the room temperature (RT) elongation is 37%, and the room temperature (RT) area reduction percentage (ROA) is 45%. Thus, the alloy having a composition within the teachings of the present application in the solution annealed + aged condition has a room temperature (RT) ultimate tensile strength (UTS) equal to about 0.96 times the room temperature (RT) ultimate tensile strength (UTS) of alloy 740H, a room temperature (RT) yield strength (YS) equal to about 0.95 times the room temperature (RT) yield strength (YS) of alloy 740H, a room temperature (RT) elongation equal to about 0.95 times the room temperature (RT) elongation of alloy 740H, and a room temperature (RT) area reduction percentage (ROA) equal to about 0.82 times the room temperature (RT) area reduction percentage (ROA) of alloy 740H. Moreover, the Co content in the alloy having a composition within the teachings of the present application is only about 0.125 times the Co content of alloy 740H.

[0065] Referring to Tables 5 and 6 below, RT tensile data for samples tested under the 700°C / 1000h / AC condition is shown.

[0066] Heat UTS, ksi UTS, MPa YS, KSI YS, MPa Elong. ROA Heat 1 179.5 1237.7 114.8 791.5 25 29 Heat 2 175.7 1211.5 108.2 746.0 26 28 Heat 3 183.4 1264.5 116.8 805.3 27 32 Heat 4 181 1248.0 114.6 790.2 24 26 Heat 5 176.2 1214.9 110.4 761.2 24 25 Heat 6 179 1234.2 113.2 780.5 25 31 Heat 8 176.9 1219.7 109.9 757.8 25 31 Heat 9 181.8 1253.5 119.3 822.6 23 24 Heat 10 184.8 1274.2 116.3 801.9 19 22 Heat 11 184.1 1269.4 114.7 790.9 22 28 Heat 12 186 1282.5 117.7 811.5 19 20 Heat 13 185 1275.6 116.5 803.3 23 28 Heat 14 182.7 1259.7 114.4 788.8 23 29 Heat 15 177.3 1222.5 109.2 752.9 21.8 21.1 Heat 15 176.5 1217.0 108.7 749.5 23.9 21.5 Heat 16 182.1 1255.6 112.6 776.4 24.4 224 Heat 16 180.6 1245.2 111.8 770.9 18.2 19.5 Heat 17 189.9 1309.4 121.3 836.4 21.1 19.2 Heat 17 187.8 1294.9 121.6 838.4 17.6 17.3 Heat 18 188.6 1300.4 120.8 832.9 17.4 15.9 Heat 18 188.6 1300.4 124.3 857.0 17.8 14.7 Heat 7 180.7 1245.9 114.2 787.4 25.3 24.7 Heat 7 180 1241.1 113.2 780.5 26.4 25.3 Heat 19 181.2 1249.4 117.6 810.9 26 29

[0067] Table 5

[0068] Heat UTS,ksi UTS, MPa YS, KSI YS, MPa Elong. ROA Heat 22 184.0 1268.7 118.4 816.4 25.1 27.8 Heat 22 183.9 1268.0 119.8 826.0 25.6 31.7 Heat 21 182.5 1258.3 115.2 794.3 25.3 26.4 Heat 21 181.8 1253.5 118.0 813.6 26.0 29.2 Heat 20 181.4 1250.8 116.7 804.6 27.4 32.1 Heat 20 181.3 1250.1 114.6 790.2 26.8 30.6

[0069] Table 6

[0070] As shown in Tables 5 and 6, the minimum room temperature (RT) ultimate tensile strength (UTS) of Heats 2, 5, 6, 7, 10, 12, and 20-21 is 1211.5 MPa (175.7 ksi), the minimum room temperature (RT) yield strength (YS) (ksi) is 746 MPa (108.2 ksi), the minimum room temperature (RT) elongation is 19%, and the minimum room temperature (RT) area reduction percentage (ROA) is 20%. That is, in some embodiments, the alloy having a composition within the teachings of the present application has a minimum room temperature (RT) ultimate tensile strength (UTS) of 1211.5 MPa (175.7 ksi), a minimum room temperature (RT) yield strength (YS) of 746 MPa (108.2 ksi), a minimum RT elongation of 19%, and a minimum room temperature (RT) area reduction percentage (ROA) of 19% under 700°C / 1000h / AC conditions. In contrast, the RT elongation of Heats 16 and 18 at 700°C / 1000h / AC is less than 19%, and the room temperature (RT) area reduction percentage (ROA) of Heats 16, 17, and 18 at 700°C / 1000h / AC is less than 20%. In addition, the room temperature (RT) ultimate tensile strength (UTS) of commercial alloy Heat 19 at 700°C / 1000h / AC is 1249.4MPa (181.2ksi), the RT0.2% yield strength (YS) is 810.9MPa (117.6ksi), the room temperature (RT) elongation is 26%, and the room temperature (RT) area reduction percentage (ROA) is 29%. Thus, at 700°C / 1000h / AC, an alloy having a composition within the range taught herein has a room temperature (RT) ultimate tensile strength (UTS) equal to about 0.97 times the room temperature (RT) yield strength (YS) of alloy 740H, a room temperature (RT) yield strength (YS) equal to about 0.92 times the room temperature (RT) yield strength (YS) of alloy 740H, a room temperature (RT) elongation equal to about 0.73 times the room temperature (RT) elongation of alloy 740H, and a room temperature (RT) percent reduction in area (ROA) equal to about 0.69 times the room temperature (RT) percent reduction in area (ROA) of alloy 740H.

[0071] Tables 7 and 8 show the RT tensile data of the samples under the 700°C / 5000h / AC condition.

[0072] Heat UTS, ksi UTS, MPa YS, KSI YS, MPa Elong. ROA Heat 1 182.1 1255.6 109.9 757.8 23 21 Heat 2 179.2 1235.6 106.2 732.2 25 27 Heat 3 184.1 1269.4 112.6 776.4 24 26 Heat 4 183.8 1267.3 110.2 759.8 23 22 Heat 5 179.3 1236.3 106 730.9 23 25 Heat 6 180.8 1246.6 108.6 748.8 24 26 Heat 8 178.1 1228.0 106.9 737.1 24 29 Heat 9 182 1254.9 112 772.2 20 19 Heat 10 188 1296.3 114.2 787.4 19 21 Heat 11 185.6 1279.7 111 765.3 21 22 Heat 12 185.6 1279.7 117.7 811.5 17 18 Heat 13 184.5 1272.1 113 779.1 22 28 Heat 14 183.1 1262.5 111.6 769.5 21 24 Heat 19 183.7 1266.6 110.1 759.1 26 30

[0073] Table 7

[0074] Heat UTS,ksi UTS, MPa YS, KSI YS, MPa Elong. ROA Heat 22 183.7 1266.6 116.3 801.9 21.8 21.7 Heat 22 183.9 1268.0 114.8 791.5 23.1 21.4 Heat 21 181.7 1252.8 111.1 766.0 22.2 22.9 Heat 21 181.9 1254.2 109.6 755.7 21.3 20.2 Heat 20 179.4 1237.0 108.0 744.7 24.1 22.7 Heat 20 180.1 1241.8 115.4 795.7 25.4 27.6

[0075] Table 8

[0076] As shown in Tables 7 and 8, Heats 2, 5, 6, 10, 12, and 20-22 (Heat 7 was not tested) have a minimum room temperature (RT) ultimate tensile strength (UTS) of 1235.6 MPa (179.2 ksi), a minimum room temperature (RT) yield strength (YS) of 730.9 MPa (106.0 ksi), a minimum room temperature (RT) elongation of 17%, and a minimum room temperature (RT) area reduction percentage (ROA) of 18%. That is, in some embodiments, the alloy having a composition within the teachings of the present application has a minimum room temperature (RT) ultimate tensile strength (UTS) of 1235.6 MPa (179.2 ksi), a minimum room temperature (RT) yield strength (YS) of 730.9 MPa (106 ksi), a minimum room temperature (RT) elongation of 17%, and a minimum room temperature (RT) area reduction percentage (ROA) of 18% under 700°C / 5000h / AC conditions. In addition, the room temperature (RT) ultimate tensile strength (UTS) of commercial alloy No. 19 at 700°C / 5000h / AC is 1266.6 MPa (183.7 ksi), RT0.2% YS is 759.1 MPa (110.1 ksi), the room temperature (RT) elongation is 26%, and the RT percentage ROA is 30%. Thus, an alloy having a composition within the range taught herein has, at 700°C / 5000h / AC, a room temperature (RT) ultimate tensile strength (UTS) equal to about 0.98 times the room temperature (RT) ultimate tensile strength (UTS) of alloy 740H, a room temperature (RT) yield strength (YS) equal to about 0.96 times the room temperature (RT) yield strength (YS) of alloy 740H, a room temperature (RT) elongation equal to about 0.65 times the room temperature (RT) elongation of alloy 740H, and a room temperature (RT) percent reduction in area (ROA) equal to about 0.60 times the room temperature (RT) percent reduction in area (ROA) of alloy 740H.

[0077] Tables 9 and 10 show the 700°C (1292°F) tensile data for samples in the solution annealed + aged condition.

[0078]

[0079] Table 9

[0080] Heat Temp.,F Temp.,C UTS, ksi UTS,Mpa YS, KSI YS, MPa Elong. ROA Heat 21 1292 700 141.2 973.6 101.2 697.4 14.1 17.7 Heat 21 1292 700 133.7 921.9 100.6 693.6 12.5 6.1 Heat 20 1292 700 135.0 930.8 99.7 687.4 17.8 20.1

[0081] Table 10

[0082] As shown in Tables 9 and 10, the heats (i.e., Heats 2, 5, 6, 7, 10, 12, and 20-21) having compositions within the teachings of the present application under solution annealing + aging conditions have a minimum ultimate tensile strength (UTS) of 909.5 MPa (131.9 ksi) at 700°C, a minimum yield strength (YS) of 651.6 MPa (94.5 ksi) at 700°C, a minimum elongation of 16.7% at 700°C, and a minimum reduction in area (ROA) of 19.5% at 700°C. That is, in some embodiments of the present application, the alloy having a composition within the teaching range of the present application under solution annealing + aging conditions has a minimum ultimate tensile strength (UTS) of 909.5 MPa (131.9 ksi) at 700°C, a minimum yield strength (YS) of 651.6 MPa (94.5 ksi) at 700°C, a minimum elongation of 16.7% at 700°C, and a minimum reduction in area (ROA) of 19.5% at 700°C. In comparison, the elongation at 700℃ of Heat 1 under solution annealing + aging conditions was 11.3%, and the reduction in area at 700℃ (ROA) was 15.3%. The elongation at 700℃ of Heat 3 under solution annealing + aging conditions was 15.2%, and the reduction in area at 700℃ (ROA) was 16.4%. The elongation at 700℃ and the reduction in area at 700℃ (ROA) of Heat 11 under solution annealing + aging conditions were both 9.5%, and the elongation at 700℃ and the reduction in area at 700℃ (ROA) of Heat 13 under solution annealing + aging conditions were both 9.5%. The 700℃ elongation under the condition of solution annealing + aging is 15.0%, and the 700℃ area reduction percentage (ROA) is 16.5%. The average 700℃ elongation of Heat 17 under the condition of solution annealing + aging (2 samples) is 14.7%, and the 700℃ area reduction percentage (ROA) is 19.0%. The average 700℃ elongation of Heat 18 under the condition of solution annealing + aging (2 samples) is 15.0%, and the 700℃ area reduction percentage (ROA) is 18.3%.

[0083] In addition, the commercial alloy heat 19 has a 700°C UTS of 960.5 MPa (139.3 ksi), a 700°C 0.2% YS of 630.2 MPa (91.4 ksi), a 700°C elongation of 29.5%, and a 700°C area reduction (ROA) of 30% in the solution annealed + aged condition. Therefore, in the solution annealed + aged condition, the alloy having a composition in the range taught in the present application has a 700°C UTS equal to about 0.95 times the 700°C UTS of alloy 740H, a 700°C yield strength (YS) equal to about 1.0 times the 700°C yield strength (YS) of alloy 740H, a 700°C elongation equal to about 0.57 times the 700°C elongation of alloy 740H, and a 700°C area reduction (ROA) equal to about 0.65 times the 700°C area reduction (ROA) of alloy 740H.

[0084] Tables 11 and 12 show the 700°C (1292°F) tensile data for samples at the 700°C / 1000h / AC condition.

[0085]

[0086] Table 11

[0087] Heat Temp., F Temp.,C UTS, ksi UTS, MPa YS, KSI YS, MPa Elong. ROA Heat 22 1292 700 140.9 971.5 106.9 737.1 24 24.7 Heat 21 1292 700 140.5 968.7 106.7 735.7 26.5 28.8 Heat 21 1292 700 137.4 947.4 101.2 697.8 20.4 28.7 Heat 20 1292 700 147.5 1017.0 101.5 699.8 22.8 27.3

[0088] Table 12

[0089] As shown in Tables 11 and 12, under the condition of 700°C / 1000h / AC, Heats 2, 5, 6, 10, 12 and 20-21 (Heat 7 was not tested) had a minimum 700°C UTS of 983.9 MPa (142.7 ksi), a minimum 700°C YS of 681.2 MPa (98.8 ksi), a minimum 700°C elongation of 20.5%, and a minimum 700°C ROA of 22.0%. That is, in some embodiments of the present application, the alloy having the composition within the teaching range of the present application has a minimum 700°C UTS of 983.9 MPa (142.7 ksi), a minimum 700°C yield strength (YS) of 681.2 MPa (98.8 ksi), a minimum 700°C elongation of 20.5%, and a minimum 700°C area reduction percentage (ROA) of 22.0% under the condition of 700°C / 1000h / AC. In comparison, Heat 11 has an elongation of 15.0% at 700°C and a reduction in area (ROA) of 16.5% at 700°C / 1000h / AC. In addition, commercial alloy Heat 19 has a UTS of 987.4MPa (143.2ksi) at 700°C, a 0.2% yield strength (YS) of 686.7MPa (99.6ksi) at 700°C, an elongation of 25.5% at 700°C, and a reduction in area (ROA) of 31% at 700°C / 1000h / AC. Thus, an alloy having a composition within the range taught herein at 700°C / 1000h / AC has a 700°C UTS equal to about 1.0 times the 700°C UTS of Alloy 740H, a 700°C yield strength (YS) equal to about 1.0 times the 700°C yield strength (YS) of Alloy 740H, a 700°C elongation equal to about 0.80 times the 700°C elongation of Alloy 740H, and a 700°C reduction in area (ROA) equal to about 0.71 times the 700°C reduction in area (ROA) of Alloy 740H.

[0090] Tables 13 and 14 show the 700°C (1292°F) tensile data for samples under the 700°C / 5000h / AC condition.

[0091]

[0092] Table 13

[0093] Heat Temp., F Temp.,C UTS,ksi UTS,Mpa YS, KSI YS, MPa Elong. ROA Heat 20 1382 750 120.2 828.8 91.6 631.6 28.2 33.2 Heat 20 1382 750 111.1 766.0 95.0 655.0 22.2 29.6 Heat 21 1382 750 111.0 765.3 92.4 637.1 21.2 27.4 Heat 21 1382 750 109.1 752.2 92.0 634.3 28.5 29.6 Heat 22 1382 750 108.4 747.4 85.0 586.1 23.8 24.7 Heat 22 1382 750 108.1 745.3 90.2 621.9 21.3 29.3

[0094] Table 14

[0095] As shown in Tables 13 and 14, under the condition of 700°C / 5000h / AC, Heats 2, 5, 6, 10, 12 and 20-22 (Heat 7 was not tested) had a minimum 700°C UTS of 940.5 MPa (136.4 ksi), a minimum 700°C YS of 667.4 MPa (96.8 ksi), a minimum 700°C elongation of 20.0%, and a minimum 700°C ROA of 26.0%. That is, in some embodiments of the present application, the alloy having a composition within the teaching range of the present application has a minimum 700°C UTS of 940.5 MPa (136.4 ksi), a minimum 700°C yield strength (YS) of 667.4 MPa (96.8 ksi), a minimum 700°C elongation of 20.0%, and a minimum 700°C area reduction percentage (ROA) of 26.0% under the condition of 700°C / 5000h / AC. In comparison, Heat 11 at 700°C / 5000h / AC had an elongation of 18.0% at 700°C and a reduction in area (ROA) of 22.5% at 700°C.

[0096] In addition, commercial alloy heat 19 has a 700°C UTS of 948.8 MPa (137.6 ksi), a 700°C 0.2% yield strength (YS) of 686.1 MPa (99.5 ksi), a 700°C elongation of 26.5%, and a 700°C ROA of 37.5% under the 700°C / 5000h / AC condition. Thus, at the 700°C / 5000h / AC condition, an alloy having a composition within the range taught herein has a 700°C UTS equal to about 0.99 times the 700°C UTS of alloy 740H, a 700°C yield strength (YS) equal to about 0.97 times the 700°C yield strength (YS) of alloy 740H, a 700°C elongation equal to about 0.76 times the 700°C elongation of alloy 740H, and a 700°C reduction in area (ROA) equal to about 0.69 times the 700°C reduction in area (ROA) of alloy 740H.

[0097] See Table 15, which shows the RT impact test data for samples in the solution annealed + aged condition.

[0098] Heat Mean Ft.Lb Average J / cm2 Heat 1 47.7 80.9 Heat 2 57.1 96.8 Heat 3 57.1 96.8 Heat 4 56.2 95.3 Heat 5 51.3 87.0 Heat 6 63.6 107.8 Heat 8 45.8 77.6 Heat 9 45.3 76.8 Heat 10 61.6 104.4 Heat 11 54.5 92.4 Heat 12 59.1 100.2 Heat 13 64.3 109.0 Heat 14 66.5 112.7 Heat 15 79.5 134.8 Heat 16 96.1 162.8 Heat 17 104.6 177.4 Heat 18 79.5 134.8 Heat 7 71.6 121.3 Heat 19 67.7 114.7

[0099] Table 15

[0100] As shown in Table 15, the composition heats (i.e., Heats 2, 5, 6, 7, 10, and 12) having the range taught by the present application under the solution annealing + aging condition have a minimum impact energy of 87.0 J / cm 2(51.3 Ft.lb). That is, in some embodiments of the present application, the alloy having a composition within the teaching range of the present application has a minimum room temperature (RT) impact energy of 87.0 J / cm2 under solution annealing + aging conditions. 2 (51.3 Ft.lb). In comparison, the RT impact energy of Heat 1 in the solution annealed + aged condition was 80.9 J / cm 2 (47.7ft.1b), the RT impact energy of Heat 8 under solution annealing + aging conditions is 77.6J / cm 2 (45.8ft.1b), the RT impact energy of Heat 9 under solution annealing + aging conditions is 76.8J / cm 2 (45.3ft.1b). In addition, the RT impact energy of commercial alloy heat 19 in the solution annealed + aged condition is 114.7J / cm 2 (67.7 ft.lb). Thus, an alloy having a composition within the teachings of the present application has an RT impact energy in the solution annealed + aged condition equal to about 0.76 times the RT impact energy of Alloy 740H.

[0101] Tables 16 and 17 show the RT impact test data of the samples under the conditions of 700° C. / 1000 h / AC.

[0102] Heat Mean Ft.Lb <![CDATA[Mean Joules / Cm 2 > Heat 1 18.3 31.1 Heat 2 24.0 40.7 Heat 3 20.7 35.0 Heat 4 13.7 23.2 Heat 5 18.3 31.1 Heat 6 33.3 56.5 Heat 8 18.3 31.1 Heat 9 17.0 28.8 Heat 10 14.7 24.9 Heat 11 24.3 41.2 Heat 12 14.0 23.7 Heat 13 29.7 50.3 Heat 14 17.3 29.4 Heat 15 10.2 17.3 Heat 16 9.3 15.7 Heat 17 7.9 13.4 Heat 18 7.2 12.3 Heat 7 15.1 25.5 Heat 19 14.3 24.3

[0103] Table 16

[0104] Heat Mean Ft.Lb. <![CDATA[Mean J / cm 2 > Heat 22 18.7 31.7 Heat 21 18.8 31.9 Heat 20 24.4 41.4

[0105] Table 17

[0106] As shown in Tables 16 and 17, the minimum RT impact energy of the heats having compositions within the teachings of the present application (i.e., Heats 2, 5, 6, 7, 10, 12, and 20-22) at 700°C / 1000h / AC is 23.7 J / cm 2 (14.0Ft.1b). That is, in some embodiments of the present application, the alloy having a composition within the teaching range of the present application has a minimum RT impact energy of 23.7 J / cm2 under the conditions of 700°C / 1000h / AC. 2 (14.0 Ft.lb). In comparison, the RT impact energy of Heat 4 at 700°C / 1000h / AC was 23.2 J / cm 2 (13.7ft.lb), Heat 15 RT impact energy at 700℃ / 1000h / AC is 17.3J / cm 2 (10.2ft.lb), Heat 16 RT impact energy at 700℃ / 1000h / AC is 15.7J / cm2 (9.3ft.lb), Heat 17 RT impact energy at 700℃ / 1000h / AC is 13.4J / cm 2 (7.9ft.lb), Heat 18 RT impact energy at 700℃ / 1000h / AC is 12.3J / cm 2 (7.2 ft.lb). In addition, the RT impact energy of commercial alloy heat 19 at 700°C / 1000h / AC is 24.3 J / cm 2 (14.3 ft.lb) Thus, the alloy having a composition within the range taught in the present application has an RT impact energy in the solution annealed + aged condition equal to about 0.98 times the 700°C RT impact energy of Alloy 740H.

[0107] Referring to Table 18, stress rupture data of samples in solution annealing + aging condition at 700°C (1292°F) are shown. As shown in Table 18, the minimum stress rupture life of Heats 2, 5, 6, 10 and 12 (Heat 7 was not tested) in solution annealing + aging condition at 393.7 MPa (57.1 ksi) stress and 700°C (1292°F) temperature is 1396 hours (h). In contrast, the stress rupture lives of Heats 1, 3, 8, 9, 11, 13 and 14 in solution annealing + aging condition at 700°C (1292°F) and 393.7 MPa (57.1 ksi) load are 1197.5 hours, 1055 hours, 1124.5 hours, 1079 hours, 464 hours, 678 hours and 692 hours, respectively.

[0108]

[0109] Table 18

[0110] In addition, the alloy having a composition within the teachings of the present application has a minimum stress rupture life at a temperature of 700°C (1292°F) in the solution annealed + aged condition equal to about 0.99 times the minimum stress rupture life of Alloy 740H at a stress of 393.7 MPa (57.1 ksi) at a temperature of 700°C (1292°F) (estimated based on the composition of the known data for Alloy 740H).

[0111] As discussed above with respect to Tables 1-18, the teachings of the present application provide Ni-based alloys having a desired combination of mechanical properties and low Co content. That is, the teachings of the present application provide a Ni-based alloy having mechanical properties similar to those of Alloy 740H, but with significantly less Co and, therefore, reduced cost. Specifically, alloys having compositions within the scope of the teachings of the present application have a room temperature (RT) ultimate tensile strength (UTS) of at least 0.96 times the room temperature (RT) ultimate tensile strength (UTS) of Alloy 740H, a room temperature (RT) yield strength (YS) of at least 0.92 times the room temperature (RT) yield strength (YS) of Alloy 740H, a room temperature (RT) elongation of at least 0.65 times the room temperature (RT) elongation of Alloy 740H, and a room temperature (RT) reduction in area percentage (ROA) of at least 0.60 times the room temperature (RT) reduction in area percentage (ROA) of Alloy 740H. In addition, alloys having compositions within the range taught herein have a 700°C UTS of at least 0.95 times the 700°C UTS of Alloy 740H, a 700°C yield strength (YS) of at least 0.97 times the 700°C elongation of Alloy 740H, and a 700°C percent reduction in area (ROA) of at least 0.65 times the 700°C ROA of Alloy 740H. And the alloy having a composition within the teaching range of the present application has an RT impact energy equal to at least 0.76 times the RT impact energy of alloy 740H, and a stress rupture life at the same pressure and temperature (700°C (1292°F) temperature and 393.7 MPa (57.1 ksi) pressure) equal to at least 0.99 times the stress rupture life of alloy 740H at 700°C (1292°F) temperature and 393.7 MPa (57.1 ksi). The stress rupture life of alloy 740H at 700°C (1292°F) and 393.7 MPa (57.1 ksi). Therefore, compared with alloy 740H, this alloy is a low-cost alloy with high-temperature mechanical and corrosion resistance characteristics, suitable for environments or industries such as USC and A-USC boilers, and power systems using supercritical CO2 (sCO2) as a heat transfer medium. The alloy can be used for high-temperature fasteners, springs and valves. In addition, the high nickel content gives the alloy good weldability and machinability.

[0112] Figure 1-2 shows a SEM (scanning electron microscope) image of a stress fracture sample from one heat, Figure 3Results from energy dispersive spectroscopy (EDS) are shown. Based on the EDS analysis, two (2) types of precipitates were identified. First, precipitates of Nb, Ti and carbides were identified, and secondly, precipitates of Cr and Mo were identified. As shown, the grain boundaries of the alloy according to the present application are clearly defined, and in some embodiments of the present application, the grain size is ASTM #2-4, and the average grain size is about 100 μm. SEM and X-ray diffraction analysis show that chromium-rich carbides (M23C6) are mainly present on the grain boundaries, wherein MC-type carbonitrides (rich in Nb, Ti) are mainly located within the grains.

[0113] Unless otherwise expressly indicated herein, all numerical values ​​expressing mechanical / thermal properties, composition percentages, dimensions and / or tolerances, or other characteristics are to be understood as being modified by the word "about" or "approximately" when describing the scope of the present application. Such modifications are necessary for a variety of reasons, including industrial practice, materials, manufacturing and assembly tolerances, and testing capabilities.

[0114] As used herein, the phrase at least one of A, B, and C should be construed to mean a logical (A or B or C), using a non-exclusive logical "or", and should not be construed to mean "at least one of A, at least one of B, and at least one of C."

[0115] The description of the present application is merely exemplary in nature, and therefore, changes that do not depart from the essence of the present application are intended to fall within the scope of the present application. These changes should not be regarded as departing from the spirit and scope of the present application.

Claims

1. An alloy comprising: A composition, wherein the composition comprises, by weight percentage: 1.3% to 1.8% aluminum, 1.5% to 4.0% cobalt, 18.0% to 22.0% chromium, 4.0% to 10.0% iron, 1.0% to 3.0% molybdenum, 1.0% to 2.5% niobium, 1.3% to 1.8% titanium, 0.8% to 1.2% tungsten, 0.01% to 0.08% carbon, and the balance nickel and incidental impurities; wherein the alloy has a stress rupture life of at least 300 hours at a temperature of 700°C and a pressure of 393.7 MPa; The room temperature elongation of the alloy after aging at 700° C. for 1000 hours is at least 19%.

2. The alloy according to claim 1, wherein The cobalt content is 2.0% to 3.0%.

3. The alloy according to claim 1, wherein The molybdenum content is 1.0% to 2.75%.

4. The alloy according to claim 1, wherein The niobium content is 1.0% to 1.75%.

5. The alloy according to claim 1, wherein The cobalt content is 2.0% to 3.0%, and the molybdenum content is 1.0% to 2.75%.

6. The alloy according to claim 1, wherein The cobalt content is 2.0% to 3.0%, and the niobium content is 1.0% to 1.75%.

7. The alloy according to claim 1, wherein The content of molybdenum is between 1.0% and 2.75%, and the content of niobium is between 1.0% and 1.75%.

8. The alloy according to claim 1, wherein The cobalt content is 2.0% to 3.0%, the molybdenum content is 1.0% to 2.75%, and the niobium content is 1.0% to 1.75%.

9. The alloy according to claim 1, wherein The alloy has a stress rupture life of at least 500 hours at a temperature of 700° C. and a pressure of 393.7 MPa.

10. The alloy according to claim 1, wherein The alloy has a room temperature elongation of at least 20% after aging at 700°C for 1000 hours.

11. The alloy according to claim 1, wherein The alloy has a room temperature elongation of at least 22% after aging at 700°C for 1000 hours.

12. The alloy according to claim 1, wherein The alloy has a room temperature elongation of at least 17% after aging at 700°C for 5000 hours.

13. The alloy according to claim 1, wherein The alloy has a room temperature elongation of at least 20% after aging at 700°C for 5000 hours.

14. The alloy according to claim 1, wherein The alloy has a room temperature impact energy of at least 12 foot-pounds (ft-lb) after aging at 700°C for 1000 hours.

15. The alloy according to claim 14, wherein The room temperature impact energy of the alloy after aging at 700°C for 1000 hours is at least 15 foot-pounds (ft-lb).

16. The alloy according to claim 15, wherein The room temperature impact energy of the alloy after aging at 700°C for 1000 hours is at least 20 foot-pounds (ft-lb).

17. The alloy according to claim 1, wherein The room temperature impact energy of the alloy after aging at 700°C for 5000 hours is at least 10 foot-pounds (ft-lb).

18. The alloy according to claim 1, wherein The room temperature impact energy of the alloy after aging at 700°C for 5000 hours is at least 12 foot-pounds (ft-lb).

19. The alloy according to claim 1, wherein The room temperature impact energy of the alloy after aging at 700°C for 5000 hours is at least 15 foot-pounds (ft-lb).

20. The alloy of claim 1, wherein The room temperature (RT) ultimate tensile strength of the alloy is between 160 ksi and 175 ksi, the room temperature (RT) 0.2% yield strength of the alloy is between 95 ksi and 115 ksi; and, after annealing the alloy at 788° C. for 4 hours and air cooling, the room temperature elongation of the alloy is between 30% and 45%.

21. The alloy according to claim 20, wherein The room temperature (RT) ultimate tensile strength is between 160 ksi and 170 ksi, the room temperature (RT) 0.2% yield strength is between 95 ksi and 110 ksi; and the room temperature elongation is between 35% and 45% after annealing the alloy at 788°C for 4 hours and air cooling.

22. The alloy of claim 1, wherein The room temperature (RT) ultimate tensile strength is between 175 ksi and 195 ksi, the room temperature (RT) 0.2% yield strength is between 105 ksi and 125 ksi; and the room temperature elongation is between 19% and 30% after annealing the alloy at 788°C for 4 hours and air cooling, and aging at 700°C for 1000 hours and air cooling.

23. The alloy according to claim 22, wherein The room temperature (RT) ultimate tensile strength is between 175 ksi and 185 ksi, the room temperature (RT) 0.2% yield strength is between 105 ksi and 120 ksi; and the room temperature elongation is between 22% and 30% after annealing the alloy at 788°C for 4 hours and air cooling, and aging at 700°C for 1000 hours and air cooling.

24. The alloy of claim 1, wherein The room temperature (RT) ultimate tensile strength is between 170 ksi and 200 ksi, the room temperature (RT) 0.2% yield strength is between 100 ksi and 120 ksi; and the room temperature elongation is between 16% and 30% after annealing the alloy at 788°C for 4 hours and air cooling, and aging at 700°C for 5000 hours and air cooling.

25. The alloy according to claim 24, wherein The room temperature (RT) ultimate tensile strength is between 175 ksi and 190 ksi, the room temperature (RT) 0.2% yield strength is between 105 ksi and 115 ksi; and the room temperature elongation is between 20% and 30% after annealing the alloy at 788°C for 4 hours and air cooling, and aging at 700°C for 5000 hours and air cooling.

26. The alloy of claim 1, wherein The ultimate tensile strength of the alloy at 700°C is between 130 ksi and 155 ksi, the 0.2% yield strength of the alloy at 700°C is between 90 ksi and 105 ksi; and, after annealing the alloy at 788°C for 4 hours and air cooling, the elongation of the alloy at 700°C is between 9% and 25%.

27. The alloy of claim 1, wherein The ultimate tensile strength of the alloy at 700°C is between 125 ksi and 140 ksi, the 0.2% yield strength of the alloy at 700°C is between 90 ksi and 100 ksi; and, after annealing the alloy at 788°C for 4 hours and air cooling, the elongation of the alloy at 700°C is between 14% and 20%.

28. The alloy of claim 1, wherein The ultimate tensile strength of the alloy at 700°C is between 135 ksi and 155 ksi, the 0.2% yield strength of the alloy at 700°C is between 95 ksi and 110 ksi; and, after annealing the alloy at 788°C for 4 hours and air cooling, and aging at 700°C for 1000 hours and air cooling, the elongation of the alloy at 700°C is between 12% and 30%.

29. The alloy according to claim 28, wherein The ultimate tensile strength of the alloy at 700°C is between 135 ksi and 150 ksi, the 0.2% yield strength of the alloy at 700°C is between 95 ksi and 105 ksi; and, after annealing the alloy at 788°C for 4 hours and air cooling, and aging at 700°C for 1000 hours and air cooling, the elongation of the alloy at 700°C is between 15% and 30%.

30. The alloy of claim 1, wherein The ultimate tensile strength of the alloy at 700°C is between 130 ksi and 150 ksi, the 0.2% yield strength of the alloy at 700°C is between 90 ksi and 110 ksi; and, after annealing the alloy at 788°C for 4 hours and air cooling, and aging at 700°C for 5000 hours and air cooling, the elongation of the alloy at 700°C is between 15% and 28%.

31. The alloy of claim 30, wherein The ultimate tensile strength of the alloy at 700°C is between 130 ksi and 145 ksi, the 0.2% yield strength of the alloy at 700°C is between 90 ksi and 102 ksi; and, after annealing the alloy at 788°C for 4 hours and air cooling, and aging at 700°C for 5000 hours and air cooling, the elongation of the alloy at 700°C is between 15% and 25%.

32. The alloy of claim 1, further comprising: 0.02% to 0.3% manganese; 0.05% to 0.3% silicon; 0.005% to 0.2% vanadium; 0.005% to 0.2% zirconium; 0.001% to 0.025% boron; and 0.001% to 0.02% nitrogen.

Citation Information

Patent Citations

  • Ni-BASED HEAT-RESISTANT ALLOY AND METHOD FOR MANUFACTURING SAME

    CN110291216A